COGNITIVE AND ETHICAL FAILURES IN AI-BASED SCIENTIFIC REVIEWING: COGNITIVE AND ETHICAL FAILURES IN AI-BASED SCIENTIFIC REVIEWING - Nikolova, Silviya; Tsankov, Tsvetoslav (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
The paper explores the ethical and cognitive implications of using artificial intelligence in the scientific peer-review process. It analyzes a real case of a hastily conducted pseudo-review, revealing inconsistencies and methodological errors that arise when automation replaces human judgment. International publishing standards from IEEE, Elsevier, Springer Nature, Wiley, and Cambridge University Press are examined to highlight the inadmissibility of AI-generated reviews and the importance of human responsibility in scientific evaluation. The study further discusses the educational context of applying AI and CAD software in teaching solid geometry, emphasizing that technology should assist, not replace, human thinking. Based on the observed deficiencies, the article proposes the development of an improved cognitive platform for independent AI-assisted reviewing, supported by expert human oversight to preserve integrity and trust in scientific communication.